An Amorphous (Al0.12Ga0.88)2O3 Deep Ultraviolet Photodetector - Shu-Bai Liu; Shoou-Jinn Chang; Sheng-Po Chang; Chia-Hsun Chen (IEEE Photonics Journal)
The authors report the deposition of an (AlxGa1-x)2O3 amorphous thin film on sapphire substrates by sputter deposition. An amorphous deep ultraviolet (UV) (Al0.12Ga0.88)2O3 photodetector, with a cutoff wavelength at 230 nm, was also fabricated. With −10 V applied bias, it was found the dark leakage current and the linear dynamic range (LDR) of the fabricated photodetector were about 1.23 × 10−9 A and 59.51 dB, respectively. With the same −10 V applied bias, the UVC/UVA contrast ratio was larger than 20. With λillumination = 230 nm and −5 V applied bias, it was found noise equivalent power (NEP) and detectivity (D*) of the fabricated amorphous deep UV (Al0.12Ga0.88)2O3 photodetector were 9.94 × 10−11 W and 2.11 × 1010 cmHz1/2W−1, respectively. These results suggest the fabricated amorphous deep UV (Al0.12Ga0.88)2O3 photodetector herein indicate a cost-effective solution for developing DUV photodetector applications.